Chronic suppurative osteomyelitis due to dislocation of the silicone prosthesis in the chin: case report - da-Silva, Ruan Soares; Rodrigues, Lizandra Gonzaga; Tostes, Camille Fonseca; de-Moraes, Larissa Cristina Araújo; Manzi, Flávio Ricardo; Vespasiano, Amaro Ilídio (Journal of Oral Diagnosis, 2022)
Introduction: Osteomyelitis is one of the inflammatory processes that spread in medullary spaces or cortical surfaces, being one of the adverse effects in cases of foreign bodies. Treatment of osteomyelitis includes antibiotic therapy, drainage and surgical interventions. Objective: The objective of this present study is to present a case report of chronic suppurative osteomyelitis, caused by the displacement of a silicone prosthesis in the chin region. Materials and methods: Case report, with information obtained through interviews with the patient, review of medical records, complementary diagnostic imaging exam and literature review. Results: Based on the information collected with the pacient, review of medical records, complementary diagnostic imaging exam and literature review, it was possible to diagnose the presence of chronic suppurative osteomyelitis in the chin region due to displacement of the silicone prosthesis. Conclusion: Aesthetic procedures are increasingly common, but without planning, proper management, correct choice of materials used and good adaptation of the prostheses in the sites, they can cause serious injuries, such as osteomyelitis, bring risks and affect the individuals quality of life. Osteomyelitis treatment is usually specific to each case and depends on a correct and early diagnosis and can be performed clinically and through imaging exams, mainly cone beam computed tomography because it has more accurate images. Treatments can range from antibiotics to resection of the affected bone.